ANIMATING CYCLING EVENT SIMULATION BY IFS FRACTAL MODEL Based on Cloning and Scaling Techniques - Darmanto, Tedjo (Fakultas Teknik Universitas Persada Indonesia YAI, 2018)
There is a tricky way to animate rotational effect of two different fractal objects as parts of a single multi-objectof fractal. From the multi-object point of view, both the individual events are looked like as a single simultaneousevent such as in the rotational simulation of two rotating wheels as the front and rear wheels and a rotated wheelof the pedal wheel in a bicycle. The above rotational effect can be created by metamorphic animation methods onthe fractal object which has IFS code in rotational IFS code family. The identical but differ in position object canbe constructed by means of cloning technique and the identical but differ in size and position can be constructedby means of the cloning and scaling techniques. To accomplish the simulation of cycling event of a bicycle in thefractal model, a combination method between metamorphic animation on multi-object and object is proposed.